Ultrahigh-strength cold-rolled steel sheet and method for producing same

By controlling the carbon distribution and carbon content in austenite, and using rapid cooling and reheating heat treatment to form phase change-induced plastic steel, the problems of microstructure inhomogeneity and residual austenite stability in the prior art are solved, and the problem of steel microstructure in the existing technology is achieved. Ultra-high strength cold-rolled steel plate with high strength and high elongation.

CN119403949APending Publication Date: 2025-02-07HYUNDAE STEEL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280096580.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-31
Filing Date
2022-12-05
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art is difficult to ensure both high strength and high elongation steels, especially when martensite is used as the matrix structure, the inhomogeneity of the microstructure and the stability of residual austenite become bottlenecks.

Method used

By controlling the carbon distribution and carbon content in austenite, the phase change-induced plastic steel is formed by rapid cooling and reheating heat treatment, ensuring that the area ratio of martensite-autenite grains is within the appropriate range, and through multiple cooling and partition heat treatment to refine and stabilize residual austenite.

Benefits of technology

Achieved yield strength of 1180MPa or greater, tensile strength of 1470MPa or greater, elongation of 15% or greater, yield ratio of 75% or greater, and flexural properties of 3.0 or less ensures the steel High strength and high moldability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403949A_ABST
    Figure CN119403949A_ABST
Patent Text Reader

Abstract

Provided are an ultra-high-strength cold-rolled steel sheet having high strength and elongation by controlling the microstructure, and a method for manufacturing the same. According to the embodiment of the invention, ultra high strength cold rolled steel sheet comprising, in wt%: 0.28% to 0.45% carbon (C), 1.0% to 2.5% silicon (Si), 1.5% to 3.0% manganese (Mn), 0.01% to 0.05% aluminum (Al), 0% (exclusive) to 1.0% (inclusive) chromium (Cr), 0% (exclusive) to 0.5% (inclusive) molybdenum (Mo), a sum of 0% (exclusive) to 0.1% (inclusive) niobium (Nb), titanium (Ti) and vanadium (V), 0% (exclusive) to 0.03% (inclusive) phosphorus (P), 0% (exclusive) to 0.03% (inclusive) sulfur (S), 0% (exclusive) to 0.01% (inclusive) The present invention relates to a steel sheet which comprises a steel sheet (1), a steel sheet (2), a steel sheet (3), a steel sheet (4), a steel sheet (5), a steel sheet (6), nitrogen (N), and the balance being iron (Fe) and other unavoidable impurities, and which satisfies a yield strength (YP) of 1180 MPa or more, a tensile strength (TS) of 1470 MPa or more, an elongation (El) of 15% or more, a yield ratio (YR) of 75% or more, and a bendability (R / t) of 3.0 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The technical idea of ​​the present invention relates to a cold-rolled steel sheet, and more particularly to an ultra-high strength cold-rolled steel sheet whose microstructure is controlled to have high strength and elongation, and a method for manufacturing the same. Background Art

[0002] In order to achieve the purpose of collision safety and weight reduction of automobiles, the structural materials of automobiles require high strength and high formability. There are dual-phase steels composed of ferrite and martensite structures, and transformation-induced plasticity steels (TRIPs) that utilize the phase transformation effect in the residual austenite phase transformation process to meet high strength and formability. Since the TRIP whose matrix structure is composed of ferrite and bainite is disadvantageous in ensuring strength according to the law of mixtures, the high-strength TRIP using martensite as the matrix structure is receiving attention. The method for manufacturing high-strength TRIP based on martensite can be achieved by rapid cooling and reheating (quenching and partitioning, QP) to achieve martensite or tempered martensite and residual austenite structures.

[0003] High-strength and high-formability steel of 1.2 GPa or more, especially 1.5 GPa or more, requires not only tensile strength but also yield strength, and requires an appropriate fraction of retained austenite structure and stability of retained austenite to ensure elongation. In the case of the prior art, there is a limitation in simultaneously ensuring a tensile strength of 1470 MPa or more and an elongation of 15% or more.

[0004] In addition, when the microstructure consists only of martensite and retained austenite, the microstructure fraction is overly sensitive to the rapid cooling endpoint temperature. In particular, even in the case of unavoidable micro-component deviations (such as casting segregation), the martensite fraction will differ due to the Ms temperature and the rapid cooling temperature, making it difficult to uniformly produce a uniform microstructure and retained austenite. In addition, martensite or tempered martensite is used as the main microstructure to ensure high strength and formability, and elongation is ensured by the retained austenite or ferrite structure. The characteristic of rapid cooling and reheating is that the microstructure fractions of tempered martensite, martensite and retained austenite vary according to the rapid cooling final temperature. In order to ensure the target properties, the optimal rapid cooling endpoint temperature interval is determined according to the alloy composition to control the microstructure fraction. If the rapid cooling endpoint temperature is too low, the size of the retained austenite becomes fine, but its fraction becomes very small. If the rapid cooling end point temperature is too high, the size of austenite becomes large, carbon enrichment is insufficient, and after final cooling, it transforms into a martensitic structure or becomes unstable, which makes little contribution to ensuring elongation.

[0005] Therefore, in order to ensure formability, an appropriate fraction of retained austenite (fine shape) and stability through carbon enrichment should be ensured. Meanwhile, in high-strength steels of 1470 MPa or more, using ferrite to ensure elongation may result in a decrease in yield strength or tensile strength, so ferrite should be limited.

[0006] As a related document, there is Korean Patent Application No. 10-2018-0047388. Summary of the invention

[0007] Technical issues

[0008] Therefore, the present invention has been accomplished in view of the above problems, and an object of the present invention is to provide an ultra-high strength cold-rolled steel sheet whose microstructure is controlled to have high strength and elongation, and a method for manufacturing the same.

[0009] It will be understood that the technical issues are provided only as examples, and the technical ideas of the present application are not limited thereto.

[0010] Technical Solution

[0011] According to one aspect of the present invention, the above object and other objects can be achieved by providing an ultra-high strength cold-rolled steel sheet having a controlled microstructure to have high strength and elongation and a method for manufacturing the same.

[0012] According to another aspect of the present invention, there is provided an ultra-high strength cold-rolled steel sheet, which comprises, by weight%, carbon (C): 0.28% to 0.45%; silicon (Si): 1.0% to 2.5%; manganese (Mn): 1.5% to 3.0%; aluminum (Al): 0.01% to 0.05%; chromium (Cr): greater than 0% and less than or equal to 1.0%; molybdenum (Mo): greater than 0% and less than or equal to 0.5%; niobium ( The total of Nb), titanium (Ti) and vanadium (V): greater than 0% and less than or equal to 0.1%; phosphorus (P): greater than 0% and less than or equal to 0.03%; sulfur (S): greater than 0% and less than or equal to 0.03%; nitrogen (N): greater than 0% and less than or equal to 0.01%, and the balance is Fe and other inevitable impurities, wherein when observing 100 μm in the width direction of the steel plate in the area between the surface portion and the center portion of the cold-rolled steel plate 2 or greater area, the ratio (B / A) of the area of ​​grains having a carbon content of 0.5% or less in austenite to the area (A) of austenite is less than 0.1, and the ultra-high strength cold-rolled steel sheet satisfies a yield strength (YP) of 1180 MPa or greater, a tensile strength (TS) of 1470 MPa or greater, an elongation (El) of 15% or greater, a yield ratio (YR) of 75% or greater, and a bendability (R / t) of 3.0 or less.

[0013] According to an embodiment of the present invention, a ratio (C / A) of an area (C) of martensite-austenite (MA) grains to an area (A) of austenite may be less than 0.5.

[0014] According to an embodiment of the present invention, when retained austenite grains are observed in a region (t / 4 thickness) between a surface portion and a center portion of a cold-rolled steel sheet in a width direction of the steel sheet using electron backscatter diffraction (EBSD) analysis, and based on an arbitrary region of the retained austenite grains, the distribution of the average value of the crystal orientation difference in the retained austenite grains is calculated by making the average value (K) of the crystal orientation difference obtained by averaging the crystal orientation differences between comparison regions adjacent to the region correspond to the region, the maximum value (Kmax), the minimum value (Kmin) and the average value (Kavg) of the crystal orientation difference in the regional distribution of the average value in the range of 0° to 3° may satisfy the relationship of (Kmax-Kavg) / (Kmax-Kmin)>0.4.

[0015] According to an embodiment of the present invention, when retained austenite grains are observed in a region between a surface portion and a central portion of a cold-rolled steel plate (t / 4 thickness) using electron backscatter diffraction (EBSD) analysis in a width direction of the steel plate, a comparison region adjacent to the region may include a first comparison region in contact with the region, a second comparison region based on the region being farther away from the region than the first comparison region and in contact with the first comparison region, and a third comparison region based on the region being farther away from the region than the second comparison region and in contact with the second comparison region, and based on an arbitrary region in the retained austenite grains, an average crystal orientation difference value obtained by averaging the crystal orientation differences between the comparison regions adjacent to the region may be an average crystal orientation difference value obtained by averaging the differences between the crystal orientations of the third comparison region and the arbitrary region.

[0016] According to an embodiment of the present invention, the ultra-high strength cold-rolled steel sheet may include a mixed structure of ferrite, tempered martensite, martensite, retained austenite, upper bainite and lower bainite. The fraction of ferrite may be in the range of greater than 0% and less than or equal to 5%, the fraction of martensite may be in the range of greater than 0% and less than or equal to 20%, the fraction of retained austenite may be in the range of 10% to 30%, the fraction of upper bainite may be in the range of greater than 0% and less than or equal to 30%, the fraction of lower bainite may be in the range of greater than 0% and less than or equal to 30%, and the fraction of tempered martensite may be the remaining fraction. The minimum value of the sum of the fraction of upper bainite and the fraction of lower bainite may be 10%.

[0017] According to an embodiment of the present invention, the ultra-high strength cold-rolled steel sheet may include a mixed structure of tempered martensite, martensite, retained austenite, upper bainite and lower bainite, wherein the fraction of martensite is in the range of greater than 0% and less than or equal to 20%, the fraction of retained austenite is in the range of 10% to 30%, the fraction of upper bainite is in the range of greater than 0% and less than or equal to 30%, the fraction of lower bainite is in the range of greater than 0% and less than or equal to 30%, and the fraction of tempered martensite is the remaining fraction.

[0018] According to an embodiment of the present invention, the average diameter of retained austenite may be 1.0 μm or less.

[0019] Beneficial effects

[0020] According to the technical idea of ​​the present invention, the ultra-high strength cold-rolled steel sheet is a phase transformation induced plastic steel formed by rapid cooling and reheating heat treatment. By performing heat treatment between hot rolling and cold rolling to properly control the carbon distribution, and by properly controlling the carbon content in the austenite after cold rolling and heat treatment, the ultra-high strength cold-rolled steel sheet can have a yield strength of 1180MPa or more, a high tensile strength of 1470MPa or more, an elongation of 15% or more, a yield ratio of 75% or more, and a bending workability (R / t) of 3.0 or less based on 90-degree bending. The ultra-high strength cold-rolled steel sheet contains tempered martensite, upper bainite and lower bainite deformation structures as microstructures, thereby refining and stabilizing the retained austenite, and stably providing yield strength and yield ratio.

[0021] In particular, multiple stages of inducing phase transformations (e.g., martensite transformation (first), lower bainite transformation (second), upper bainite transformation (third)) during rapid cooling (second cooling), rapid cooling retention, reheating, and partitioning can help control the problem of structural inhomogeneity caused by casting segregation, etc. (which is inevitably present in steel), and can refine and stabilize the retained austenite. When composed only of martensite and retained austenite, the Ms point may change due to the compositional inhomogeneity of the structure (e.g., casting segregation), and at the same rapid cooling temperature, the martensite and retained austenite fractions may be different. However, the ultra-high strength cold-rolled steel sheet according to the technical idea of ​​the present invention can solve these problems.

[0022] The effects of the present invention are described only as examples, and the scope of the present invention is not limited by these effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1The concept of a method of calculating an average value (K) of crystal orientation differences by averaging crystal orientation differences between comparison regions adjacent to one region according to the method of manufacturing an ultra-high strength cold-rolled steel sheet according to an embodiment of the present invention is shown, and Figure 2 The distribution pattern of the average value (K) of the crystal orientation difference is shown.

[0024] Figure 3 : is a scanning electron microscope photograph showing the microstructure of the steel after the first heat treatment of Example 1 in the experimental example of the present invention.

[0025] Figure 4 The scanning electron microscope photograph shows the microstructure of the steel of Comparative Example 2 after the first heat treatment in the experimental example of the present invention.

[0026] Figure 5 A scanning electron microscope photograph showing the final microstructure of the ultra-high strength cold-rolled steel sheet of Example 1 in the experimental examples according to the present invention.

[0027] Figure 6 A scanning electron microscope photograph showing the final microstructure of the ultra-high strength cold-rolled steel sheet of Comparative Example 1 in the experimental examples according to the present invention.

[0028] Figure 7 A scanning electron microscope photograph showing the final microstructure of the ultra-high strength cold-rolled steel sheet of Comparative Example 2 in the experimental examples according to the present invention.

[0029] Figure 8 A scanning electron microscope photograph showing the final microstructure of the ultra-high strength cold-rolled steel sheet of Comparative Example 3 in the experimental examples according to the present invention.

[0030] Fig. 9 The shape and distribution of retained austenite in the final microstructure of the ultra-high strength cold-rolled steel sheet of Example 1 in the experimental examples according to the present invention are shown by EBSD.

[0031] Fig.10 The shape and distribution of retained austenite in the final microstructure of the ultra-high strength cold-rolled steel sheet of Comparative Example 1 in the experimental examples according to the present invention are shown by EBSD.

[0032] Fig.11 The shape and distribution of retained austenite in the final microstructure of the ultra-high strength cold-rolled steel sheet of Comparative Example 2 in the experimental examples according to the present invention are shown by EBSD. DETAILED DESCRIPTION

[0033] The preferred embodiments of the present invention will be described in detail below with reference to the attached drawings. The embodiments of the present invention are provided to explain the technical idea of ​​the present application more completely to those skilled in the art, and the following embodiments can be modified in a variety of different forms, but the scope of the technical idea of ​​the present application is not limited to the following embodiments. On the contrary, the embodiments are provided to make the present application thorough and complete, and to fully convey the technical idea of ​​the present application to those skilled in the art. In the specification, the same reference numerals represent the same elements. In addition, various elements and regions in the drawings are schematically drawn. Therefore, the technical idea of ​​the present invention is not limited by the relative sizes or spacings drawn in the attached drawings.

[0034] The technical idea of ​​the present invention provides an ultra-high strength cold-rolled steel plate and a method for manufacturing the same, wherein the ultra-high strength cold-rolled steel plate has a yield strength of 1180 MPa or greater, a tensile strength of 1470 MPa or greater, an elongation of 15% or greater, a yield ratio (yield strength / tensile strength) of 75% or greater, and a 90-degree bending workability of 3.0R / t or less.

[0035] Hereinafter, the technical idea of ​​the ultra-high strength cold-rolled steel sheet according to the present invention is described in detail.

[0036] On a wt % basis, the ultra-high strength cold-rolled steel sheet according to an embodiment of the present invention comprises: carbon (C): 0.28% to 0.45%; silicon (Si): 1.0% to 2.5%; manganese (Mn): 1.5% to 3.0%; aluminum (Al): 0.01% to 0.05%; chromium (Cr): greater than 0% and less than or equal to 1.0%; molybdenum (Mo): greater than 0% and less than or equal to 0.5%; the sum of niobium (Nb), titanium (Ti) and vanadium (V): greater than 0% and less than or equal to 0.1%; phosphorus (P): greater than 0% and less than or equal to 0.03%; sulfur (S): greater than 0% and less than or equal to 0.03%; nitrogen (N): greater than 0% and less than or equal to 0.01%, and the balance is Fe and other inevitable impurities.

[0037] Hereinafter, the role and content of each component contained in the ultra high strength cold rolled steel sheet according to the present invention are described. Here, the content of each constituent element means weight % based on the total weight of the steel sheet.

[0038] Carbon (C): 0.28% to 0.45%

[0039] Carbon is added to ensure the strength of the steel, and in particular, it improves the strength of the martensitic structure. In addition, a sufficient carbon content is required because it can be classified to stabilize austenite and ensure elongation through the transformation induced plasticity (TRIP) effect. When the carbon content is less than 0.28%, it may be difficult to obtain the target strength and elongation at the same time. When the carbon content is greater than 0.45%, weldability may be reduced and hydrogen embrittlement may occur. Therefore, it is preferred that the carbon content is 0.28% to 0.45% based on the total weight of the steel plate.

[0040] Silicon (Si): 1.0% to 2.5%

[0041] Silicon is a ferrite stabilizing element that delays the formation of carbides in ferrite and martensite and has a solid solution strengthening effect. In particular, it is important to delay the formation of carbides in martensite and separate carbon into austenite. When the silicon content is less than 1.0%, it may be difficult to fully ensure the stability of the retained austenite because the carbide formation inhibition effect is small. When the silicon content is greater than 2.5%, due to the formation of oxides (such as Mn) during the manufacturing process, 2 SiO 4 ), so the plating properties may be impaired, and the carbon equivalent may increase, thereby reducing weldability. Therefore, it is preferred that silicon is added in an amount of 1.0% to 2.5% of the total weight of the steel sheet.

[0042] Manganese (Mn): 1.5% to 3.0%

[0043] Manganese has a solid solution strengthening effect and improves hardenability, delaying the formation of ferrite and bainite during cooling. When the manganese content is less than 1.5%, the effect of adding manganese may be insufficient, making it difficult to ensure hardenability. When the manganese content is more than 3.0%, the transformation of bainite may be excessively delayed, the workability may be reduced due to the formation or segregation of inclusions (such as MnS), and the weldability may be reduced due to the increase in carbon equivalent. Therefore, it is preferred to add manganese in an amount of 1.5% to 3.0% of the total weight of the steel plate.

[0044] Aluminum (Al): 0.01% to 0.05%

[0045] Aluminum acts as a deoxidizer and, similar to silicon, can help suppress carbide formation. When the content of aluminum is less than 0.01%, the deoxidation effect may be insufficient. When the content of aluminum is more than 0.05%, AlN may be formed during slab manufacturing, which may cause cracks during casting or hot rolling. Therefore, it is preferred that aluminum is added in an amount of 0.01% to 0.05% based on the total weight of the steel plate.

[0046] Chromium (Cr): greater than 0% and less than or equal to 1.0%

[0047] Chromium has a solid solution strengthening effect, contributes to strength improvement by improving hardenability, and works together with C and Mn to refine martensite and bainite structures and stabilize retained austenite. When the chromium content is greater than 1.0%, the transformation of bainite may be excessively delayed, and the manufacturing cost of steel may increase. Therefore, it is preferred to add chromium in an amount greater than 0% and less than or equal to 1.0% of the total weight of the steel plate.

[0048] Molybdenum (Mo): greater than 0% and less than or equal to 0.5%

[0049] Molybdenum has a solid solution strengthening effect, contributes to strength improvement by improving hardenability, and works together with C and Mn to refine martensite and bainite structures and stabilize retained austenite. When the content of molybdenum is greater than 0.5%, the transformation of bainite may be excessively delayed, and the manufacturing cost of steel may increase. Therefore, it is preferred to add molybdenum in an amount greater than 0% and less than or equal to 0.5% of the total weight of the steel plate.

[0050] Total of niobium (Nb), titanium (Ti) and vanadium (V): greater than 0% and less than or equal to 0.1% The present invention may include at least one of niobium, titanium and vanadium. Niobium, titanium and vanadium are precipitate forming elements, which can improve strength through precipitation strengthening effect, and can also obtain grain refinement effect. When the total amount of niobium, titanium and vanadium is added in an amount greater than 0.1%, the manufacturing cost of the steel may increase significantly, the rolling load may increase significantly due to a large amount of precipitation during rolling, and the elongation may decrease. Therefore, the total amount of niobium, titanium and vanadium is preferably greater than 0% and less than or equal to 0.1% of the total weight of the steel plate, respectively. In addition, it is preferred that each of niobium, titanium and vanadium is added in an amount of 0.1% or less of the total weight of the steel plate. For example, each of niobium, titanium and vanadium can be added in an amount greater than 0% and less than or equal to 0.05%.

[0051] Phosphorus (P): greater than 0% and less than or equal to 0.03%

[0052] Phosphorus is an impurity contained in the manufacturing process of steel, and although it can contribute to improving strength through solid solution strengthening, it may cause low-temperature embrittlement when contained in a large amount. Therefore, it is preferred that the content of phosphorus is limited to more than 0% and less than or equal to 0.03% based on the total weight of the steel plate.

[0053] Sulfur (S): greater than 0% and less than or equal to 0.03%

[0054] Sulfur is an impurity included in the steel manufacturing process and can form non-metallic inclusions such as FeS and MnS, thereby reducing bendability, toughness and weldability. Therefore, it is preferred that the sulfur content be limited to greater than 0% and less than or equal to 0.03% based on the total weight of the steel plate.

[0055] Nitrogen (N): greater than 0% and less than or equal to 0.01%

[0056] Nitrogen is an element inevitably contained in the process of steel manufacturing and can help stabilize austenite, but it may react with Al to form AlN, which may cause cracks during operation. Therefore, it is preferred to limit the content of nitrogen to more than 0% and less than or equal to 0.01% of the total weight of the steel plate.

[0057] Meanwhile, in addition to the above-mentioned alloy elements, the ultra high strength cold rolled steel sheet according to the variant embodiment of the present invention may further include at least one of elements having the following composition ranges.

[0058] Nickel (Ni): greater than 0% and less than or equal to 0.5%

[0059] Nickel can help stabilize austenite and improve the hardenability of steel. When the content of nickel is greater than 0.5%, it increases the manufacturing cost of steel, which is undesirable. Therefore, it is preferred to add nickel in a content greater than 0% and less than or equal to 0.5% of the total weight of the steel plate.

[0060] Copper (Cu): greater than 0% and less than or equal to 0.5%

[0061] Copper can help stabilize austenite and improve the hardenability of steel. When the content of copper is greater than 0.5%, it increases the manufacturing cost of steel, which is undesirable. Therefore, it is preferred to add copper in a content greater than 0% and less than or equal to 0.5% of the total weight of the steel plate.

[0062] Furthermore, it is preferred that the total amount of nickel and copper be added in a content greater than 0% and less than or equal to 1.0%.

[0063] Boron (B): greater than 0% and less than or equal to 0.005%

[0064] Boron can improve hardenability like Mn, Cr and Mo. When the content of boron is greater than 0.005%, it may be concentrated on the surface and cause deterioration of quality (such as plating adhesion). Therefore, it is preferred to add boron in an amount greater than 0% and less than or equal to 0.005% of the total weight of the steel sheet.

[0065] The remaining component of the ultra-high strength cold rolled steel sheet is iron (Fe). However, since unexpected impurities in raw materials or the surrounding environment may be inevitably mixed in the normal steelmaking process, they cannot be excluded. Since these impurities are known to technicians in the field of ordinary manufacturing processes, they are not specifically mentioned in this specification.

[0066] The ultra-high strength cold-rolled steel sheet according to the embodiment of the present invention may include a mixed structure of ferrite, tempered martensite, martensite, residual austenite, upper bainite and lower bainite. The fraction of ferrite may be 0% to 5% (including 0%), the fraction of martensite may be greater than 0% and less than or equal to 20%, the fraction of residual austenite may be 10% to 30%, the fraction of upper bainite may be greater than 0% and less than or equal to 30%, the fraction of lower bainite may be greater than 0% and less than or equal to 30%, and the fraction of tempered martensite may be the remaining fraction. The minimum value of the sum of the fraction of upper bainite and the fraction of lower bainite may be 10%. The fraction means the area ratio obtained from the microstructure photograph by an image analyzer. Ferrite may include polygonal ferrite. In addition, the average diameter of the residual austenite may be, for example, 1.0 μm or less, for example, 0.1 μm to 1.0 μm.

[0067] The retained austenite is finely distributed in the laths and grain boundaries of the tempered martensite and bainite, so that the retained austenite can be stabilized, and the strength and elongation can be stably ensured.

[0068] In addition, the ultra-high strength cold-rolled steel sheet may not contain ferrite. In this case, the ultra-high strength cold-rolled steel sheet may contain a mixed structure of tempered martensite, martensite, residual austenite, upper bainite and lower bainite. The fraction of martensite may be greater than 0% and less than or equal to 20%, the fraction of residual austenite may be 10% to 30%, the fraction of upper bainite may be greater than 0% and less than or equal to 30%, the fraction of lower bainite may be greater than 0% and less than or equal to 30%, and the fraction of tempered martensite may be the remaining fraction. In addition, the sum of the fraction of upper bainite and the fraction of lower bainite may be 10% to 60%. The minimum value of the sum of the fraction of upper bainite and the fraction of lower bainite may be 10%.

[0069] In the ultra-high strength cold-rolled steel sheet according to the technical idea of ​​the present invention, when observing 100 μm in the width direction (TD) of the cold-rolled steel sheet in the area (t / 4 thickness) between the surface portion and the center portion of the steel sheet, 2 or greater, the ratio (B / A) of the area of ​​the grains having a carbon content of 0.5% or less in austenite to the area of ​​the austenite (A) is less than 0.1. The ratio (B / A) can be understood as a measure of the composition stability of the retained austenite (RA) generated in the steel sheet. When the ratio (B / A) is 0.1 or greater, the composition stability of the austenite is insufficient, and thus the effect of improving the elongation due to the retained austenite cannot be obtained. In order to measure the carbon content in a single grain, the lattice interplanar spacing is measured by transmission electron microscopy (TEM) observation, and the relationship C is used. γ =(αγ-3.592) / 0.033 gives the carbon content. γis the austenite lattice constant measured by transmission electron microscopy.

[0070] In the ultra-high strength cold-rolled steel sheet according to the technical idea of ​​the present invention, when observing 100 μm in the width direction (TD) of the cold-rolled steel sheet in the area (t / 4 thickness) between the surface portion and the center portion of the steel sheet, 2 When the area of ​​the martensite-austenite grains is 0.5 or more, the ratio (C / A) of the area of ​​the martensite-austenite grains (C) to the area of ​​the austenite (A) is less than 0.5. The ratio (C / A) can be understood as a measure of the stability of each portion of the retained austenite (RA) generated in the steel plate. When the ratio (C / A) is 0.5 or more, the martensite-austenite grains that do not participate in the transformation-induced martensite transformation become excessive, and thus sufficient elongation and work hardenability cannot be obtained.

[0071] When the retained austenite grains are observed in the region (t / 4 thickness) between the surface portion and the center portion of the ultra-high strength cold-rolled steel sheet according to the technical idea of ​​the present invention in the width direction (TD) of the steel sheet using electron backscatter diffraction (EBSD) analysis, and the distribution of the average value of the crystal orientation difference in the retained austenite grains is calculated based on one arbitrary region of the retained austenite grains by making the average value (K) of the crystal orientation difference obtained by averaging the crystal orientation difference between the comparison regions adjacent to the region correspond to the region, the maximum value (Kmax), the minimum value (Kmin) and the average value (Kavg) of the crystal orientation difference in the regional distribution of the average value in the range of 0° to 3° satisfy the relationship of (Kmax-Kavg) / (Kmax-Kmin)>0.4. At the same time, the maximum value of (Kmax-Kavg) / (Kmax-Kmin) is 1.

[0072] Figure 1 The concept of a method of calculating an average value (K) of crystal orientation differences by averaging crystal orientation differences between comparison regions adjacent to one region according to the method of manufacturing an ultra-high strength cold-rolled steel sheet according to an embodiment of the present invention is shown, and Figure 2 The distribution pattern of the average value (K) of the crystal orientation difference is shown.

[0073] refer to Figure 1 When the retained austenite grains are observed in the region between the surface portion and the center portion of the cold-rolled steel sheet in the width direction of the steel sheet using an electron backscatter diffraction (EBSD) analysis method, the region (A 0 ) may include a comparison region adjacent to region (A 0 ) contacted with the first comparison area (A 1 To A 6 ), based on region (A 0 ) than the first comparison area (A 1To A 6 ) is further away from the region and is closer to the first comparison region (A 1 To A 6 ) contacted with the second comparison area (A 7 To A 18 ), and area-based (A 0 ) than the second comparison area (A 7 To A 18 ) is further away from the region and is closer to the second comparison region (A 7 To A 18 ) contacted with the third comparison area (A 19 To A 36 In this case, based on an arbitrary region (A 0 ) by comparing with the area (A 0 ) The average value (K) of the crystal orientation difference obtained by averaging the crystal orientation differences between adjacent comparison regions can be obtained based on any region (A 0 ) by comparing the third comparison area (A 19 To A 36 ) is the average value (K) of the crystal orientation difference obtained by averaging the crystal orientation differences between .

[0074] For example, based on an arbitrary region (A 0 ) by comparing the third comparison area (A 19 To A 36 The average value (K) of the crystal orientation difference obtained by averaging the crystal orientation differences between ) can be expressed by the following equation 1. Here, (MA) i Indicates the third comparison area (A 19 To A 36 ) and the region (A 0 ), n can be 19 and m can be 36.

[0075] [Equation 1]

[0076]

[0077] refer to Figure 2 The distribution of the average value (K) of the crystal orientation difference is 0° to 5°, wherein the maximum value (Kmax), minimum value (Kmin), and average value (Kavg) displayed in the region where the average value of the crystal orientation difference is 0° to 3° can be calculated.

[0078] In the method for manufacturing an ultra-high strength cold-rolled steel sheet according to the technical idea of ​​the present invention, the maximum value (Kmax), minimum value (Kmin) and average value (Kavg) shown in the distribution of the region where the average value (K) of the crystal orientation difference is 0° to 3° satisfy the relationship of (Kmax-Kavg) / (Kmax-Kmin)>0.4.

[0079] In the transformation-induced martensitic transformation reaction of austenite having an FCC structure, defects (such as dislocations or stacking defects) within the grains serve as martensite nucleation sites. Therefore, when the average value of the crystal orientation difference (which is a value indicating the defect distribution within the grains) is too small, the transformation-induced plasticity (TRIP) nucleation is insufficient, and thus the effect of improving ductility × tensile strength due to the transformation-induced martensitic transformation cannot be obtained. On the other hand, when the average value of the crystal orientation difference is too high, the desired ductility improvement effect cannot be obtained because the transformation-induced martensitic transformation occurs concentratedly at the beginning of tensile deformation.

[0080] The ultra-high strength cold-rolled steel sheet satisfying the specific composition and content range of the above-mentioned alloy composition and the above-mentioned conditions can satisfy the following conditions: for example, yield strength (YP): 1180MPa to 1330MPa, tensile strength (TS): 1470MPa to 1770MPa, elongation (El): 15% or more, yield ratio (YR): 75% or more, and bendability (R / t): 3.0 or less.

[0081] A method for manufacturing an ultra-high strength cold-rolled steel sheet according to the present invention is described hereinafter with reference to the accompanying drawings.

[0082] Method for manufacturing ultra-high strength cold-rolled steel sheet

[0083] In the manufacturing method according to the present invention, the semi-finished product as the target of the hot rolling process may be, for example, a slab. After molten steel having a predetermined composition is obtained through a steelmaking process, a slab in a semi-finished state may be secured through a continuous casting process.

[0084] The method for manufacturing an ultra-high strength cold-rolled steel sheet according to an embodiment of the present invention includes the steps of manufacturing a hot-rolled steel sheet using a steel having the composition; manufacturing a cold-rolled steel sheet by cold-rolling the hot-rolled steel sheet; annealing the cold-rolled steel sheet; cooling the cold-rolled steel sheet multiple times and performing a partitioning heat treatment on the cold-rolled steel sheet.

[0085] In particular, in order to anneal the cold-rolled steel sheet, the temperature is raised to the Ac3 temperature or higher and maintained for a period of time, and then multiple cooling consisting of two stages of slow cooling and rapid cooling is performed until the rapid cooling final temperature. Then, after maintaining the rapid cooling final temperature for a period of time, the temperature is raised to the Ms temperature or higher for partitioning heat treatment, and then the temperature is maintained at a constant level for the partitioning heat treatment time, and then finally cooled to the Mf temperature or lower.

[0086] Steps in manufacturing hot rolled steel sheets

[0087] A steel billet having the above alloy composition is prepared and reheated at a slab reheating temperature (SRT) of, for example, 1150°C to 1250°C. Through this heat treatment, the re-dissolution of segregated components and the re-dissolution of precipitates during casting may occur, thereby homogenizing the material and enabling hot rolling. When the reheating temperature is higher than 1250°C, the size of the austenite grains may increase, and the process cost may increase due to the increase in temperature. When the reheating temperature is higher than 1250°C, the size of the austenite grains may increase, and the process cost may increase due to the increase in temperature. Reheating may be performed for, for example, 1 hour to 4 hours. When the reheating time is less than 1 hour, the homogenization of the segregation may be insufficient. When the reheating time is greater than 4 hours, the size of the austenite grains may increase, and the process cost may increase due to the increase in temperature.

[0088] After reheating, hot rolling may be performed in a conventional manner, and hot finish rolling may be performed at a finish rolling outlet temperature (FDT) of, for example, 850° C. to 970° C. to produce a hot rolled steel sheet. When the FDT is lower than 850° C., ferrite or pearlite may be generated. When the FDT is higher than 970° C., scale formation increases, the grain size becomes coarse, and it may be difficult to achieve fine uniformity of the structure.

[0089] Then, the hot rolled steel sheet is cooled to a coiling temperature of, for example, 400° C. to 700° C. The cooling may be air cooling or water cooling, and may be performed at a cooling rate of, for example, 10° C. / sec to 30° C. / sec. An increased cooling rate is beneficial for reducing the average grain size. The cooling is preferably performed to the coiling temperature.

[0090] Then, the hot rolled steel sheet is coiled at a coiling temperature (CT) of, for example, 400° C. to 700° C. The range of the coiling temperature may be selected in consideration of cold rolling properties and surface properties. When the coiling temperature is lower than 400° C., a hard phase (e.g., martensite) is excessively produced, causing an excessive increase in the material of the hot rolled steel sheet, which may significantly increase the rolling load during cold rolling. When the coiling temperature is higher than 700° C., it may cause microstructural inhomogeneity in the final product.

[0091] Meanwhile, in the method for manufacturing an ultra-high strength cold-rolled steel sheet according to the technical concept of the present invention, after the hot rolling coiling, before the cold rolling, a first heat treatment may be performed at 500°C to 680°C for 10 seconds to 12 hours. Here, the first heat treatment may be selected from a batch annealing process, a continuous heat treatment process, etc. After the first heat treatment, the microstructure of the steel sheet is 100 μm 2 There are two or less carbides with a grain size of 500nm or more distributed in an area, and a pearlite ratio of 5% or less. When the first heat treatment process is not performed or the temperature is lower than 500°C, the cold rolling load increases, which increases the process difficulty. When the heat treatment process temperature is higher than 680°C or the heat treatment process time is greater than 12 hours, coarse carbides (such as spherical cementite) with a diameter of 500nm or more are formed. This may aggravate the inhomogeneity of carbon atoms and produce residual austenite with excessive dissolved carbon in the final microstructure after cold rolling. In the case of austenite with a carbon content of about 1.1% or more, the TRIP effect is expected to decrease with increasing proportion, resulting in a decrease in strength × elongation properties. Therefore, the stability of the retained austenite is adjusted by appropriately adjusting the microstructure after the first heat treatment.

[0092] Steps in manufacturing cold rolled steel sheets

[0093] The hot rolled steel sheet is pickled using an acid to remove its surface oxide scale. Then, the hot rolled steel sheet is cold rolled at an average reduction rate of, for example, 40% to 70% to form a cold rolled steel sheet. As the average reduction rate increases, the formability increases due to the microstructure refinement effect. When the average reduction rate is less than 40%, it is difficult to obtain a uniform microstructure. When the average reduction rate is greater than 70%, the rolling force increases and the process load increases. By cold rolling, the final steel sheet can have a final thickness. The cold rolled steel sheet can have a structure in which the structure of the hot rolled steel sheet is extended.

[0094] Annealing step

[0095] The cold rolled steel sheet is annealed in a continuous annealing furnace with a normal slow cooling section. Annealing is performed to form an austenite single phase structure. The annealing heat treatment temperature and time may affect the austenite grain size and, therefore, may have a significant effect on the strength of the cold rolled steel sheet.

[0096] Annealing is performed at a heating rate of, for example, 2°C / sec or more, for example, in a range of 2°C / sec to 10°C / sec. When the heating rate is less than 2°C / sec, it takes a long time to reach the target annealing temperature, which reduces production efficiency and may increase grain size.

[0097] Annealing can be performed, for example, at a temperature of Ac3 or higher, for example, in a temperature range of 830°C to 930°C, for example, in a temperature range of 830°C to 900°C, for example, for a time of 30 seconds to 120 seconds. In this heating and annealing step, the cold rolled structure is reversely transformed into austenite. When the annealing temperature is lower than 830°C, a single austenite phase cannot be formed to produce the final structure (tempered martensite). Preferably, annealing should be performed at A3 temperature or higher to form a single austenite phase. When the annealing temperature is higher than 900°C, the austenite grains may become coarser, which may reduce the strength.

[0098] As the annealing time increases, it affects the coarsening caused by austenite grain growth, just like the annealing temperature, but the effect of the annealing time is smaller than that of the annealing temperature. When the annealing time is greater than 120 seconds, the heat treatment efficiency may decrease. When the annealing time is less than 30 seconds, the annealing efficiency may be insufficient.

[0099] Multiple cooling steps

[0100] The annealed cold rolled steel sheet is cooled multiple times. The cooling step can be performed in the following two steps.

[0101] First, the annealed cold-rolled steel sheet is slowly cooled to a temperature range that suppresses the formation of ferrite, for example, a first cooling final temperature of 650° C. to 800° C., at a cooling rate of, for example, 1° C. / sec to 15° C. / sec, for example, 3° C. / sec to 10° C. / sec. When the first cooling final temperature of the slow cooling is lower than 650° C., ferrite transformation may occur in an undesirable amount, and thus the strength may be reduced. It is preferred that the fraction of ferrite generated by ferrite transformation is limited to less than 0% to 5%.

[0102] Then, the cold-rolled steel sheet that has been subjected to the first cooling (slow cooling) is subjected to the second cooling (rapid cooling) to, for example, the Ms temperature or lower temperature, for example, in the temperature range of Ms-140°C to Ms-30°C, for example, the second cooling final temperature of 180°C to 300°C by rapid cooling at a cooling rate of, for example, 20°C / second or more, for example, 20°C / second to 100°C / second. The second cooling is a rapid cooling step, and may include a 2-1 rapid cooling step and a 2-2 rapid cooling step performed in sequence. The cooling rate of the 2-1 rapid cooling step may be, for example, 20°C / second or more, and may be rapidly cooled to a temperature of Ms-30°C or lower. In this cooling, a portion of austenite is transformed into martensite, and the amount thereof is about 20% to 80%. The cooling rate of the 2-2 rapid cooling step may be, for example, 30°C / second or more, and the 2-2 rapid cooling step causes martensitic transformation by cooling to the rapid cooling end temperature (Ms-140°C to Ms-30°C).

[0103] By the second cooling (rapid cooling), a part of austenite can be transformed into martensite. The fraction of martensite produced can be 20% to 80%.

[0104] In this heat treatment, if the average cooling rate in the slow cooling to rapid cooling section can be ensured to be greater than 70° C. / sec, the 2-1 rapid cooling step and the 2-2 rapid cooling step may be performed without distinction.

[0105] Then, the cold-rolled steel sheet subjected to the second cooling (rapid cooling) is held at the second cooling final temperature, for example, for 5 to 90 seconds. During this holding time after the rapid cooling, initially, the temperature of the steel may be homogenized. Then, while it is isothermally held at the second cooling final temperature, a portion of the retained austenite may be converted into lower bainite or the like.

[0106] Partitioning heat treatment steps

[0107] The cold-rolled steel sheet that has been cooled multiple times is reheated at a heating rate of, for example, 3°C / second to 20°C / second, and is subjected to a partitioning heat treatment by maintaining the temperature in a temperature range of, for example, 360°C to 500°C, for example, 360°C to 460°C, for a time of, for example, 30 seconds to 500 seconds, for example, 30 seconds to 500 seconds.

[0108] If the partitioning heat treatment temperature is lower than 360° C., the partitioning effect may not be significant. When the partitioning heat treatment temperature is higher than 500° C., carbides may become coarse, and thus the strength may decrease.

[0109] Compared with the partitioning temperature, the partitioning heat treatment holding time has a smaller effect. When the partitioning heat treatment holding time is less than 30 seconds, it may be difficult to obtain a stable partitioning effect. When the partitioning heat treatment holding time is greater than 500 seconds, the heat treatment efficiency may decrease, the carbide size may increase, and the strength may decrease.

[0110] The partitioning heat treatment step may be performed immediately after multiple cooling steps, or after a holding period of several minutes or longer at room temperature.

[0111] After the partitioning heat treatment step is completed, it is cooled to room temperature, for example, to a temperature in the range of 0°C to 40°C.

[0112] Analysis of microstructural changes

[0113] Hereinafter, changes in the microstructure of the ultra-high-strength cold-rolled steel sheet are described in detail during the process of performing the method of manufacturing the ultra-high-strength cold-rolled steel sheet according to the technical idea of ​​the present invention.

[0114] During the annealing step, the microstructure of the cold rolled steel sheet undergoes a reverse transformation to austenite.

[0115] In the first cooling of the multiple cooling steps, the fraction of ferrite generated by ferrite transformation is limited to less than 5%, and ferrite may not be generated. If 5% or more ferrite is generated, the strength may be reduced, and thus the target strength may not be achieved.

[0116] In the second cooling of the multiple cooling steps, since the cold-rolled steel sheet is cooled at a rapid cooling rate, the ferrite transformation, pearlite transformation and bainite transformation are suppressed, and a portion of the austenite is transformed into martensite. Here, the martensite fraction produced by the martensite transformation can be limited to 20% to 80%. When the fraction of martensite produced during the second cooling process exceeds 80%, it may be difficult to ensure an appropriate amount of residual austenite fraction. When the fraction is less than 20%, the fraction of residual austenite after cooling is too high, making it difficult to ensure the stability of the residual austenite, and even if the bainite transformation structure increases, the martensite fraction may be small, resulting in reduced strength. In addition, a portion of the martensite structure may increase internal stress to increase the bainite nucleation rate, thereby rapidly performing bainite transformation, even at low temperatures of Ms or lower.

[0117] In the second cooling of the multiple cooling steps, a portion of austenite is transformed into bainite (which may be mainly lower bainite) when it is held at the second cooling final temperature after rapid cooling. In addition, fine precipitates may be formed in the martensite produced in the previous step. Here, the time held at the second cooling final temperature may be 5 seconds to 90 seconds. When the holding time is less than 5 seconds, the lower bainite transformation may not occur sufficiently. When the holding time exceeds 90 seconds, the process cost may increase due to the excessively long heat treatment time.

[0118] In the partitioning heat treatment step, carbon can diffuse and concentrate into the interior of the retained austenite, thereby stabilizing the retained austenite. In addition, a portion of the retained austenite can undergo bainite transformation. The bainite transformation can refine the shape of the retained austenite after rapid cooling, and thus can help stabilize the retained austenite. For this function, the sum of the fraction of upper bainite and the fraction of lower bainite can be 10% or more.

[0119] After the partitioning heat treatment step is performed, a portion of the unstable austenite may be transformed into martensite during the final cooling to room temperature. If a large amount of martensite is generated at this time, the fraction of the final retained austenite decreases, which may adversely affect the formability. Therefore, it is desirable to control the generated martensite to less than 20%.

[0120] In order to suppress martensitic transformation in the final cooling, it is desirable to ensure the secondary cooling final temperature, the holding time at the secondary cooling final temperature, and smoothly perform the heat treatment step, thereby refining and stabilizing the retained austenite.

[0121] Below the Ms point, there are cases where bainite transformation is not considered, but studies have shown that bainite transformation is possible even below the Ms point, and studies have shown that bainite nucleation increases more below the Ms point than at the Ms point.

[0122] After the heat treatment process, the final microstructure may contain tempered martensite (20% to 80%), retained austenite (10% to 30%), lower bainite (0% to 30%), upper bainite (0% to 30%), some ferrite (0% to 5%) or martensite (0% to 20%). The sum of the fraction of upper bainite and the fraction of lower bainite may be 10% or more. The average diameter of the retained austenite may be 1.0 μm or less.

[0123] Experimental Examples

[0124] Hereinafter, preferred experimental examples are shown to help understand the present invention. However, the following experimental examples are only intended to help understand the present invention, and the present invention is not limited to the following experimental examples.

[0125] Steel having each component (unit: weight %) of the following Table 1 was prepared, and cold-rolled steel sheets according to Examples and Comparative Examples were prepared through predetermined hot and cold rolling processes and heat treatment processes. The remainder was iron (Fe).

[0126]

Table 1

[0127]

[0128]

[0129] Referring to Table 1, steel types A to D satisfy the composition range of the present invention, specifically the following composition range based on weight %: carbon (C): 0.28% to 0.45%; silicon (Si): 1.0% to 2.5%; manganese (Mn): 1.5% to 3.0%; aluminum (Al): 0.01% to 0.05%; chromium (Cr): greater than 0% and less than or equal to 1.0%; molybdenum (Mo): greater than 0% and less than or equal to 0.5%; the sum of niobium (Nb), titanium (Ti) and vanadium (V): greater than 0% and less than or equal to 0.1%; phosphorus (P): greater than 0% and less than or equal to 0.03%; sulfur (S): greater than 0% and less than or equal to 0.03%; nitrogen (N): greater than 0% and less than or equal to 0.01%, and the balance is iron (Fe). In contrast, steel type E is outside the composition range of the present invention, and specifically does not satisfy the carbon (C) range of 0.28% to 0.45%. Table 2 shows the Ac3 temperature, Ms temperature, Ms-140°C temperature, and Ms-30°C temperature of each steel type. The unit is °C.

[0130]

Table 2

[0131] Steel Type Ac3 Ms Ms-140 Ms-30 A 830 323 183 290 B 830 323 183 290 C 819 321 181 290 D 833 339 199 309 E 845 364 224 334

[0132] Referring to Table 2, the Ac3 temperature was calculated using Thermo-Calc and the TCFE9 database. The Ms temperature was calculated using the following empirical formula. In the following empirical formula, for example, "[C]" represents the weight % of carbon. Ms (°C) = 539-423 [C] -30.4 [Mn] -12.1 [Cr] -17.7 [Ni] -7.5 [Mo]

[0133] The steel type slab was reheated at 1200° C. and held for 3 hours, hot rolled to a thickness of 2.4 mm at a finishing exit temperature of 950° C., and then coiled at 600° C. Then, the coiled hot-rolled steel sheet was pickled to remove oxide scale on the surface, and cold rolled to produce a cold-rolled steel sheet with a thickness of 1.2 mm.

[0134] Then, heat treatment was performed under the conditions of Table 3.

[0135] Table 3 shows the condition values ​​of the heat treatment process used to manufacture the cold-rolled steel sheets of the comparative example and the example. In Table 3, "first heat treatment" means a heat treatment performed after hot rolling and before cold rolling.

[0136]

Table 3

[0137]

[0138] Referring to Table 3, Examples 1 to 4 satisfy the process range of the present invention. Comparative Example 1 uses steel type E outside the composition range of the present invention, Comparative Example 2 exceeds and does not satisfy 500°C to 680°C (which is the temperature range of the first heat treatment) and is lower than and does not satisfy 830°C to 930°C (which is the annealing temperature range), and Comparative Example 3 satisfies the annealing temperature range, but exceeds and does not satisfy 30 seconds to 120 seconds (which is the annealing holding time), and is lower than and does not satisfy 5 seconds to 90 seconds (which is the rapid cooling holding time at the second cooling final temperature (180°C to 300°C) after the second cooling (rapid cooling)).

[0139] Table 4 shows the values ​​of items representing the microstructures of the cold-rolled steel sheets of the comparative example and the example.

[0140] In Table 4, the first item value (B / A) means when observing 100 μm in the width direction of the steel sheet in the area between the surface portion and the center portion of the cold-rolled steel sheet. 2or more, the ratio (B / A) of the area of ​​the grains having a carbon content of 0.5% or less in austenite to the area (A) of austenite, the second item value (C / A) means when observing 100 μm in the width direction of the steel sheet in the area between the surface portion and the center portion of the cold-rolled steel sheet 2 or larger area, the ratio (C / A) of the area (C) of the martensite-austenite grains to the area (A) of the austenite, and the third item value ((Kmax-Kavg) / (Kmax-Kmin)) represents the relationship among the maximum value (Kmax), the minimum value (Kmin) and the average value (Kavg) shown in the distribution of the region where the average value of the crystal orientation difference is 0° to 3° when the retained austenite grains are observed in the width direction of the steel plate in the region between the surface portion and the center portion of the cold-rolled steel plate by an electron backscatter diffraction (EBSD) analysis method, and when the average distribution of the crystal orientation difference within the retained austenite grains is calculated based on an arbitrary region within the retained austenite grains by making the average value of the crystal orientation difference obtained by averaging the crystal orientation differences between comparison regions adjacent to the region correspond to the region.

[0141]

Table 4

[0142] Steel Type category B / A C / A (Kmax-Kavg) / (Kmax-Kmin) A Example 1 0 0.05 0.61 B Example 2 0 0.02 0.62 C Example 3 0 0.05 0.51 D Example 4 0 0.03 0.63 E Comparative Example 1 0.2 0.01 0.38 A Comparative Example 2 0.3 0.52 0.61 D Comparative Example 3 0 0.89 0.53

[0143] Referring to Table 4, Examples 1 to 4 satisfy all of the following ranges: the first item value (B / A) <0.1, the second item value (C / A) <0.5, and the third item value ((Kmax-Kavg) / (Kmax-Kmin))>0.4. In contrast, in the case of Comparative Example 1, the first item value (B / A) is greater than 0.1, and the third item value ((Kmax-Kavg) / (Kmax-Kmin)) is less than 0.4. It can be confirmed that in the case of Comparative Example 2, the first item value (B / A) is greater than 0.1, and the second item value (C / A) is not less than 0.5. It can be confirmed that in the case of Comparative Example 3, the second item value (C / A) is not less than 0.5. Table 5 shows the physical and mechanical properties of the manufactured hot-rolled steel plates and steel pipes, such as yield strength (YS), tensile strength (TS), elongation (EL), yield ratio (YR), and 90-degree bendability (R / t).

[0144]

Table 5

[0145]

[0146]

[0147] Referring to Table 5, the examples satisfy the target ranges of yield strength (YS), tensile strength (TS), elongation (EL), yield ratio (YR), and 90 degree bendability (R / t). In addition, the TS×T.El value (which is the product of tensile strength and elongation) may be 20,000 or more, preferably 21,000 or more, and more preferably 22,000 or more. In contrast, Comparative Example 1 is lower than and does not satisfy the elongation (EL) range of 15% or more and is lower than and does not satisfy the product range of tensile strength and elongation of 20,000 or more, Comparative Example 2 is lower than and does not satisfy the elongation (EL) range of 15% or more, is lower than and does not satisfy the yield ratio (YR) range of 75% or more, is higher than and does not satisfy the 90 degree bendability (R / t) of 3.0 or less, and is lower than and does not satisfy the product range of tensile strength and elongation of 20,000 or more, Comparative Example 3 is lower than and does not satisfy the yield strength (YP) range of 1180 MPa or more, is lower than and does not satisfy the tensile strength (TS) range of 1470 MPa or more, is lower than and does not satisfy the elongation (EL) range of 15% or more, is lower than and does not satisfy the yield ratio (YR) range of 75% or more, is higher than and does not satisfy the 90 degree bendability (R / t) range of 3.0 or less, and is lower than and does not satisfy the product range of tensile strength and elongation of 20,000 or more.

[0148] The comparative examples that do not meet the target properties are examined. In the case of comparative example 1, the carbon content is characterized by being low, and it cannot simultaneously ensure a tensile strength of 1470 MPa and an elongation of 15% or more. In the case of comparative example 2, the first heat treatment temperature is high, characterized by a low annealing temperature, and the elongation cannot be sufficiently ensured. When the first heat treatment temperature is high and the annealing temperature is low, a coarse martensite-austenite composite structure is excessively formed compared to the retained austenite, and it cannot show the TRIP effect, so it is considered to be unhelpful in ensuring the elongation. In the case of comparative example 3, the rapid cooling holding time after the second cooling is too short, and the yield strength, elongation and yield ratio are relatively low. After the second cooling, the yield strength increases due to low bainite transformation or microprecipitation in the martensite during the holding process, but in this case, it is considered that the time is insufficient. Furthermore, it is considered that the austenite phase is not transformed into lower bainite, but a part of the austenite phase forms a martensite-austenite composite structure, and therefore, a martensite-austenite phase without the TRIP effect is excessively formed, which does not contribute to ensuring the elongation.

[0149] Figure 3 is a scanning electron microscope photograph showing the microstructure of the steel after the first heat treatment of Example 1 in the experimental example of the present invention, and Figure 4: is a scanning electron microscope photograph showing the microstructure of the steel after the first heat treatment of Comparative Example 2 in the experimental example of the present invention.

[0150] refer to Figure 3 and Figure 4 , for Example 1 and Comparative Example 2 having the same composition, the microstructure was observed after the first heat treatment, and in the case of Comparative Example 2, a large amount of coarse cementite having a grain size of 500 nm or more was formed. Therefore, although a large amount of retained austenite was ensured, an elongation of 15% or more could not be achieved.

[0151] Specifically, in Example 1, after the first heat treatment, the microstructure of the steel sheet was 2 There are two or more carbides with a grain size of 500nm or more distributed in the area, and the pearlite ratio is 5% or less. In Comparative Example 2, when the heat treatment process temperature is higher than 680°C, coarse carbides with a diameter of 500nm or more, such as spherical cementite, are formed. This may aggravate the heterogeneity of carbon atoms and produce residual austenite with excessive dissolved carbon in the final microstructure after cold rolling. In the case of austenite with a carbon content of about 1.1% or more, the TRIP effect decreases as the ratio increases, which deteriorates the strength × elongation properties. Therefore, it is necessary to adjust the stability of the retained austenite by appropriately adjusting the microstructure after the first heat treatment.

[0152] Figure 5 A scanning electron microscope photograph showing the final microstructure of the ultra-high strength cold-rolled steel sheet of Example 1 in the experimental examples of the present invention, Figure 6 A scanning electron microscope photograph showing the final microstructure of the ultra-high strength cold-rolled steel sheet of Comparative Example 1 in the experimental example of the present invention, Figure 7 A scanning electron microscope photograph showing the final microstructure of the ultra-high strength cold-rolled steel sheet of Comparative Example 2 in the experimental example according to the present invention, and Figure 8 A scanning electron microscope photograph showing the final microstructure of the ultra-high strength cold-rolled steel sheet of Comparative Example 3 in the experimental examples according to the present invention. Fig. 9 The shape and distribution of retained austenite in the final microstructure of the ultra-high strength cold-rolled steel sheet of Example 1 in the experimental example according to the present invention are shown by EBSD, Fig.10 shows the shape and distribution of retained austenite in the final microstructure of the ultra-high strength cold-rolled steel sheet of Comparative Example 1 in the experimental example according to the present invention by EBSD, and Fig.11The shape and distribution of retained austenite in the final microstructure of the ultra-high strength cold-rolled steel sheet of Comparative Example 2 in the experimental examples according to the present invention are shown by EBSD.

[0153] refer to Figure 5 and Fig. 9 It can be confirmed that the final microstructure of the ultra-high strength cold-rolled steel sheet according to Example 1 may include a mixed structure in which ferrite, tempered martensite, martensite, retained austenite, upper bainite and lower bainite are mixed, specifically, the main microstructure is composed of tempered martensite and upper bainite / lower bainite, and the retained austenite is distributed in the grain boundary between martensite and bainite laths. In the accompanying drawings, the phases represented by LB and T.MS represent lower bainite and tempered martensite, respectively. In addition, it can be confirmed that the fraction of ferrite is in the range of 0% to 5%, the fraction of martensite is in the range of greater than 0% and less than or equal to 20%, the fraction of retained austenite is in the range of 10% to 30%, the fraction of upper bainite is in the range of greater than 0% and less than or equal to 30%, the fraction of lower bainite is in the range of greater than 0% and less than or equal to 30%, and the fraction of tempered martensite may be included as the remaining fraction. Furthermore, it was confirmed that the average diameter of retained austenite was 1.0 μm or less.

[0154] In contrast, Figure 6 and Fig.10 and Figure 5 The difference is that the final microstructure of the ultra-high strength cold-rolled steel sheet according to Comparative Example 1 is mainly composed of tempered martensite, and the fraction of retained austenite is less than 10%. Figure 6 In the German example, the tempered martensite region is denoted as T.MS. In addition, reference Figure 7 and Fig.11 The final microstructure of the ultra-high strength cold-rolled steel sheet according to Comparative Example 2 may include a mixed structure of ferrite, tempered martensite, martensite, a martensite-austenite composite structure, retained austenite, upper bainite, and lower bainite. Figure 7 In the reference, the martensite-austenite composite structure is represented as MA. Figure 8 , the final microstructure of the ultra-high strength cold-rolled steel sheet according to Comparative Example 3 mainly consists of tempered martensite and martensite-austenite composite structure.

[0155] It will be understood by those skilled in the art that the technical idea of ​​the present invention described above is not limited to the above embodiments and the accompanying drawings, and various substitutions, changes and modifications are possible within the scope not departing from the technical idea of ​​the present invention.

Claims

1. An ultra-high strength cold-rolled steel sheet, comprising, by weight %, carbon (C): 0.28% to 0.45%; silicon (Si): 1.0% to 2.5%; manganese (Mn): 1.5% to 3.0%; aluminum (Al): 0.01% to 0.05%; chromium (Cr): greater than 0% and less than or equal to 1.0%; molybdenum (Mo): greater than 0% and less than or equal to 0.5%; the sum of niobium (Nb), titanium (Ti) and vanadium (V): greater than 0% and less than or equal to 0.1%; phosphorus (P): greater than 0% and less than or equal to 0.03%; sulfur (S): greater than 0% and less than or equal to 0.03%; nitrogen (N): greater than 0% and less than or equal to 0.01%, and the balance is Fe and other unavoidable impurities, in, When observing 100 μm in the width direction of the steel sheet in the area between the surface portion and the center portion of the cold-rolled steel sheet, 2 or more, the ratio (B / A) of the area of ​​grains having a carbon content of 0.5% or less in austenite to the area of ​​austenite (A) is less than 0.1, and The ultra-high strength cold-rolled steel sheet satisfies a yield strength (YP) of 1180 MPa or more, a tensile strength (TS) of 1470 MPa or more, an elongation (El) of 15% or more, a yield ratio (YR) of 75% or more, and a bendability (R / t) of 3.0 or less.

2. The ultra-high strength cold-rolled steel sheet according to claim 1, wherein: The ratio (C / A) of the area of ​​the martensite-austenite grains (C) to the area of ​​the austenite (A) is less than 0.

5.

3. The ultra-high strength cold-rolled steel sheet according to claim 1, wherein: When retained austenite grains are observed in a region (t / 4 thickness) between a surface portion and a center portion of a cold-rolled steel sheet in a width direction of the steel sheet using an electron backscatter diffraction (EBSD) analysis, and based on an arbitrary region of the retained austenite grains, a distribution of an average value of the crystal orientation difference in the retained austenite grains is calculated by making an average value (K) of the crystal orientation difference obtained by averaging the crystal orientation differences between comparison regions adjacent to the region correspond to the region, a maximum value (Kmax), a minimum value (Kmin) and an average value (Kavg) of the crystal orientation difference in the regional distribution of the average value in the range of 0° to 3° satisfy a relationship of (Kmax-Kavg) / (Kmax-Kmin)>0.

4.

4. The ultra-high strength cold-rolled steel sheet according to claim 3, wherein: When retained austenite grains are observed in a region between a surface portion and a center portion of a cold-rolled steel sheet (t / 4 thickness) in a width direction of the steel sheet using an electron backscatter diffraction (EBSD) analysis, a comparison region adjacent to the region includes a first comparison region in contact with the region, a second comparison region based on the region being farther from the region than the first comparison region and in contact with the first comparison region, and a third comparison region based on the region being farther from the region than the second comparison region and in contact with the second comparison region, and Based on an arbitrary region in the retained austenite grains, the average crystal orientation difference value obtained by averaging the crystal orientation differences between the comparison regions adjacent to the region is the average crystal orientation difference value obtained by averaging the differences between the crystal orientations of the third comparison region and the arbitrary region.

5. The ultra-high strength cold-rolled steel sheet according to claim 1, wherein: The ultra-high strength cold-rolled steel sheet includes a mixed structure of ferrite, tempered martensite, martensite, retained austenite, upper bainite and lower bainite.

6. The ultra-high strength cold-rolled steel sheet according to claim 5, wherein: The ferrite fraction is within the range of greater than 0% and less than or equal to 5%, The fraction of martensite is within the range of greater than 0 and less than or equal to 20%, The fraction of retained austenite is in the range of 10% to 30%, The fraction of upper bainite is within the range of greater than 0% and less than or equal to 30%, The fraction of lower bainite is in the range of greater than 0% and less than or equal to 30%, and The fraction of tempered martensite is the remaining fraction.

7. The ultra-high strength cold-rolled steel sheet according to claim 6, wherein: The minimum value of the sum of the fraction of upper bainite and the fraction of lower bainite is 10%.

8. The ultra-high strength cold-rolled steel sheet according to claim 1, wherein: The ultra-high strength cold-rolled steel sheet comprises a mixed structure of tempered martensite, martensite, retained austenite, upper bainite and lower bainite, Wherein, the fraction of martensite is in the range of greater than 0 and less than or equal to 20%, The fraction of retained austenite is in the range of 10% to 30%, The fraction of upper bainite is within the range of greater than 0% and less than or equal to 30%, The fraction of lower bainite is in the range of greater than 0% and less than or equal to 30%, and The fraction of tempered martensite is the remaining fraction.

9. The ultra-high strength cold-rolled steel sheet according to claim 5 or 8, wherein: The average diameter of retained austenite is 1.0 μm or less.

Citation Information

Patent Citations

  • Appratus for detecting electric power line state

    KR1020180047388A